Occipital Magnocellular VEP Non-linearities Show a Short Latency Interaction Between Contrast and Facial Emotion - Mu, Eveline; Crewther, David (Frontiers in Human Neuroscience, 2020)
The magnocellular system has been implicated in the rapid processing of facial emotions, such as fear. Of the various anatomical possibilities, the retino-colliculo-pulvinar route to the amygdala is currently favoured. However, it is not clear whether and when amygdala arousal activates primary visual cortex (V1). Non-linear visual evoked potentials provide a well-accepted technique for examining temporal processing in the magnocellular and parvocellular pathways in visual cortex. Here we investigated the relationship between facial emotion processing and the separable magnocellular (K2.1) and parvocellular (K2.2) components of the second order non-linear multifocal visual evoked potential responses recorded from occipital scalp (OZ). Stimuli comprised pseudorandom brightening/darkening of fearful, happy, neutral faces (or no face) with surround patches decorrelated from the central face-bearing patch. For the central patch the spatial contrast of the faces was 30% while the modulation of the per-pixel brightening/darkening was uniformly 10% or 70%. From 14 neurotypical young adults, we found a significant interaction between emotion and contrast in the magnocellularly driven K2.1 peak amplitudes, with greater K2.1 amplitudes for fearful (vs happy) faces at 70% temporal contrast condition. Taken together, our findings suggest that facial emotional information is present in early V1 processing as conveyed by the M pathway, and more activated for happy as opposed to fearful faces. An explanation is offered in terms of the contest between feedback and response gain modulation models.